Trade Liberalization along the Firm Size Distribution: The Case of the EU-South Korea FTA - Sonali Chowdhry; Gabriel J. Felbermayr (Center for Economic Studies and Ifo Institute (CESifo), 2021)
In 2011, the EU-South Korea Free Trade Agreement (EUKFTA) entered into force. With its focus on non-tariff barriers (NTBs), it is a leading example of a deep new generation agreement. Using detailed French customs data for the period 2000 to 2016, we investigate how exporters of different size have benefitted from the agreement. Applying a diff-in-diff strategy that makes use of the rich dimensionality of the data, we find that firms with larger pre-FTA sizes benefit more from the FTA than firms at the lower end of the size distribution, both at the extensive (product) and the intensive margins of trade. The latter finding is in surprising contrast to leading theories of firm-level behavior. Moreover, we find that our main result is driven by NTB reductions rather than tariff cuts. In shedding light on the distributional effects of trade agreements within exporters, our findings highlight the need for effective SME-chapters in FTAs.
Keywords: F13; F14; 330; trade policy; firm heterogeneity; firm size distribution; non-tariff barriers